A study on consumers preferences towards brand of petrol in Malaysia / Nurul Akmal Yusoff - Yusoff, Nurul Akmal (2010)
For this year 2010, all oil and gas companies in Malaysia had plans on attracting more consumers to uses their products. Due to this, the preferences level of the consumers is put into consideration as one of the purposes of the strategies to retain the current customers and attract the new potential customers as well. Malaysia petrol brand which is PETRONAS have to compete with their foreign competitors like SHELL, EXXONMOBILE, BP, and CALTEX who nowadays has extremely develop their technologies to become as one of the main prefer brand of petrol by consumers in this region. Due to that, PETRONAS as well as other oil and gas sectors has to take a full consideration in providing and giving the best service to the customers in Malaysia in order to ensure the plans successfully and achieve the target. This study is made for the purpose of to identify how far those keys factor can have an influence to consumers preferences towards brand of petrol in Malaysia. The first objective of this research is to study on the consumers preferences towards brand of petrol in Malaysia and the researcher used frequency analysis in order to get the result. Secondly the objective is to study the relationship between the dependent and independent variables and Pearson’s correlation coefficient are used to know the relationship between the variable. Thirdly, to identify the most dominant factors that contribute to the consumers’ preferences towards brand of petrol and the researcher used descriptive analysis. Lastly the objective of this research is to propose some recommendation in order to help the management. The result of this study shows the most dominant factors that influence consumers preferences towards brand of petrol and also the recommendation in order to overcome this issue.